Effects of dietary selenium on host response to necrotic enteritis in young broilers. (February 2015) - Xu, Shouzhen; Lee, Sung-Hyen; Lillehoj, Hyun S.; Hong, Yeong Ho; Bravo, David
Highlights: Optimum organic selenium dose for enhancing gut health was determined in poultry. Selenium-fed broiler chickens showed reduced serum Clostridium toxins after NE infection. Dietary selenium enhanced serum antibody levels to Clostridium toxins. Dose-dependent effect of selenium on intestinal cytokine response was shown. Feeding organic selenium enhanced intestinal beta-defensins expression. Abstract: The effects of dietary supplementation of young broiler chickens with an organic selenium (Se) formulation, B-Traxim Se, on experimental necrotic enteritis (NE) were studied. Chickens treated with three Se doses (0.25, 0.50, 1.00 mg/kg) from hatch were orally challenged with Eimeria maxima at 14 days of age followed by Clostridium perfringens to induce NE. Chickens fed with 0.50 mg/kg Se showed significantly increased body weights and antibody levels against NetB, and significantly reduced gut lesions compared with non-supplemented chickens. However, there were no significant differences in Eimeria oocyst shedding between the Se-treated and non-supplemented groups. Levels of IL-1β, IL-6, IL-8, iNOS, LITAF, TNFSF15, AvBD6, AvBD8, and AvBD13 transcripts were increased in the gut and spleen of at least one of the three Se-treated groups compared with the non-treated group. These results suggest that dietary supplementation of young broilers with Se might be beneficial to reduce the negative consequence of NE.